Effects of simulated altitude (normobaric hypoxia) on cardiorespiratory parameters and circulating endothelial precursors in healthy subjects - Ciulla, Michele M; Cortiana, Michela; Silvestris, Ilaria; Matteucci, Emanuela; Ridolfi, Elisa; Giofrè, Fabrizio; Zanardelli, Maddalena; Paliotti, Roberta; Cortelezzi, Agostino; Pierini, Alberto; Magrini, Fabio; Desiderio, Maria Alfonsina (Respiratory research, 2007)
Circulating Endothelial Precursors (PB-EPCs) are involved in the maintenance of the endothelial compartment being promptly mobilized after injuries of the vascular endothelium, but the effects of a brief normobaric hypoxia on PB-EPCs in healthy subjects are scarcely studied. Clinical and molecular parameters were investigated in healthy subjects (n = 8) in basal conditions (T0) and after 1 h of normobaric hypoxia (T1), with Inspiratory Fraction of Oxygen set at 11.2% simulating 4850 mt of altitude. Blood samples were obtained at T0 and T1, as well as 7 days after hypoxia (T2). In all studied subjects we observed a prompt and significant increase in PB-EPCs, with a return to basal value at T2. The induction of hypoxia was confirmed by Alveolar Oxygen Partial Pressure (PAO2) and Spot Oxygen Saturation decreases. Heart rate increased, but arterial pressure and respiratory response were unaffected. The change in PB-EPCs percent from T0 to T1 was inversely related to PAO2 at T1. Rapid (T1) increases in serum levels of hepatocyte growth factor and erythropoietin, as well as in cellular PB-EPCs-expression of Hypoxia Inducible Factor-1alpha were observed. In conclusion, the endothelial compartment seems quite responsive to standardized brief hypoxia, possibly important for PB-EPCs activation and recruitment.